2017
DOI: 10.1001/jamaophthalmol.2017.0245
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Haplotype in the NR3C2 Gene, Encoding the Mineralocorticoid Receptor, With Chronic Central Serous Chorioretinopathy

Abstract: IMPORTANCE Chronic central serous chorioretinopathy (cCSC) is a chorioretinal disease with unknown disease etiology. The glucocorticoid receptor and the mineralocorticoid receptor, 2 glucocorticoid-binding receptors, might be involved in the pathogenesis of cCSC.OBJECTIVE To assess the association of functional variants and haplotypes in the glucocorticoid receptor (NR3C1) and mineralocorticoid receptor (NR3C2) genes with cCSC. DESIGN, SETTING, AND PARTICIPANTSIn this case-control genetic association study, 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 45 publications
4
49
2
Order By: Relevance
“…8,9 Because corticosteroids bind to both the glucocorticoid receptor (GR) and the mineralocorticoid receptor (MR), it has been hypothesized that both are involved in the pathogenesis of CSC. 5,[9][10][11][12] Because of the plausible role of the choroidal endothelium in the pathophysiology of CSC, culturing of human choroidal endothelial cells (CECs) is of particular interest. [13][14][15][16] Endothelial cells (ECs) are heterogenic cells that show substantial sitespecific structural and biochemical variation due to their interaction with their surroundings.…”
Section: Conclusion With This Optimized Choroidal Endothelial Cell mentioning
confidence: 99%
“…8,9 Because corticosteroids bind to both the glucocorticoid receptor (GR) and the mineralocorticoid receptor (MR), it has been hypothesized that both are involved in the pathogenesis of CSC. 5,[9][10][11][12] Because of the plausible role of the choroidal endothelium in the pathophysiology of CSC, culturing of human choroidal endothelial cells (CECs) is of particular interest. [13][14][15][16] Endothelial cells (ECs) are heterogenic cells that show substantial sitespecific structural and biochemical variation due to their interaction with their surroundings.…”
Section: Conclusion With This Optimized Choroidal Endothelial Cell mentioning
confidence: 99%
“…[7][8][9][10] Several studies well documented the role of corticosteroids in CSC, referring to both glucocorticoid (cortisol) and mineralocorticoid (aldosterone) hormones. [11][12][13][14][15] Zhao and associates 16 reported that intravitreous injection of aldosterone, a specific mineralocorticoid receptor (MR) activator, induced choroidal vessel dilation and leakage in rodents' eyes. As MR antagonists reversed this effect, two specific MR antagonists (spironolactone and eplerenone) were used in the treatment of CSC with promising results in bestcorrected visual acuity (BCVA) and central macular thickness (CMT) outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In this research, we found that miR-454 expression was upregulated in OSCC samples and acted as a positive regulator in the cell viability, colony formation, invasion, and migration of OSCC cells.NR3C2, as an important downstream target gene of miR-454, was confirmed in our experiment. NR3C2 encodes a mineralocorticoid receptor (MR) that acts as a ligand-dependent transcription factor mediating the function of aldosterone in salt and water balance 28.…”
mentioning
confidence: 99%